Hey, honey an award - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2003)
Dreams don't come much sweeter than this. Honey Care Africa, a small business in Kenya supported by the International Finance Corporation, has won the first Equator Prize. Launched in 2002 by a cluster of international agencies such as IUCN (the...